LEGAL CONSEQUENCES OF SPREADING FALSE INFORMATION ABOUT A PERSON ON THE INTERNET - Yurovskyi, Andriy (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of this article is to consider problematic issues regarding the legal consequences of spreading inaccurate information about a person on the Internet, including public persons, based on the study and generalization of the doctrinal development of legal science, the current legislation of Ukraine, and court practice. The methodological basis of the research is general scientific and special methods of scientific knowledge. The use of these methods made it possible to identify and describe the legal consequences of spreading false information about a person on the Internet. Results: it was concluded that recently, in most cases, national courts refuse to satisfy claims and do not recognize information disseminated via the Internet as unreliable and do not oblige them to refute it, since in most cases courts consider judgments against plaintiffs to be evaluative and those that criticize a person, but there is no defamation at the same time, which deprives the persons to receive proper protection and satisfaction in the judicial procedure. Discussion: as noted by the Civil Court of Cassation as part of the Supreme Court in the review of judicial practice in cases on the protection of dignity, honor and business reputation, and the author of the article fully agrees with this, that national courts need to find the right balance or priority for a legal and democratic state between two constitutionally guaranteed rights: the right to freedom of thought and speech, the right to freely express one’s views and beliefs, on the one hand, and the right to respect for human dignity, guarantees of non-interference in personal and family life, judicial protection of the right to refute inaccurate information about a person, on the other hand. This is the essence of the correct resolution of a defamation dispute.